ASSIMILATION OF NITROGEN BY SOYBEAN GROWN AT DIFFERENT NITRATE-NITROGEN LEVELS - Noreen, Sibgha; Ellahi, Nosheen Noor; Mirza, Javed Iqbal (Journal of Research (Science), 2004)
Investigations were carried out to study the effects of varying levels of nitrate-nitrogen on the absorption of nitrogen by different plant parts in soybean [Glycine max (L.) Merrill] in greenhouse. The treatments were 0 mM, 2 mM, 5 mM, 10 mM KNO3. Soybean cultivar RAWAL-1 was used as test plant. Assimilation of nitrogen in shoots and roots increased with concurrent increasing levels of nitrate-nitrogen in the media. Furthermore, nitrogen content in shoot and root increased with the age of crop. Various plant parts maintained the maximum content of nitrogen in plants harvested at middle of pod growth, i.e., 10 weeks after sowing compared to that of harvested at flowering stage, i.e., 5 weeks after sowing.